1986
DOI: 10.1002/cne.902490407
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic projection from nucleus raphe dorsalis to neostriatum in the rat

Abstract: The existence of a dopamine (DA) projection from nucleus raphe dorsalis (RD) to neostriatum was demonstrated in the rat by combined tyrosine hydroxylase (TH) immunohistochemistry and radioautography after retrograde axonal transport of [3H]noradrenaline ([3H]NA). Intrastriatal injections of [3H]NA were carried out in normal rats or after ipsilateral destruction of the nigrostriatal DA system by injection of 6-hydroxydopamine (6-OHDA) into the substantia nigra. Some 1,000 TH-positive nerve cell bodies were coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
36
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 54 publications
3
36
0
2
Order By: Relevance
“…Experiments combining retrograde tracing with serotonin (5-HT) immunostaining have established that many nonserotonergic DRN neurons project extrinsically (Beitz et al, 1986;Ma et al, 1991;Petrov et al, 1992Petrov et al, , 1994 Van Bockstaele et al, 1993;Kirifides et al, 2001;Kim et al, 2004;Halberstadt and Balaban, 2006a). Nonserotonergic DRN projections are neurochemically heterogeneous, and may contain a number of transmitter substances, including glutamate (Schwarz and Schwarz, 1992;Kiss et al, 2002), dopamine (Pohle et al, 1984;Descarries et al, 1986;Yoshida et al, 1989;Stratford and Wirtshafter, 1990;Hasue and Shammah-Lagnado, 2002), GABA (Nanopoulos et al, 1982;Stamp and Semba, 1995;Ford et al, 1995;Jankowski and Sesack, 2002), nitric oxide (Xu and Hokfelt, 1997;Simpson et al, 2003), and neuropeptides such as vasoactive intestinal polypeptide (VIP) (Petit et al, 1995;Kozicz et al, 1998) and cholecystokinin Seroogy and Fallon, 1989).…”
Section: Nih Public Accessmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiments combining retrograde tracing with serotonin (5-HT) immunostaining have established that many nonserotonergic DRN neurons project extrinsically (Beitz et al, 1986;Ma et al, 1991;Petrov et al, 1992Petrov et al, , 1994 Van Bockstaele et al, 1993;Kirifides et al, 2001;Kim et al, 2004;Halberstadt and Balaban, 2006a). Nonserotonergic DRN projections are neurochemically heterogeneous, and may contain a number of transmitter substances, including glutamate (Schwarz and Schwarz, 1992;Kiss et al, 2002), dopamine (Pohle et al, 1984;Descarries et al, 1986;Yoshida et al, 1989;Stratford and Wirtshafter, 1990;Hasue and Shammah-Lagnado, 2002), GABA (Nanopoulos et al, 1982;Stamp and Semba, 1995;Ford et al, 1995;Jankowski and Sesack, 2002), nitric oxide (Xu and Hokfelt, 1997;Simpson et al, 2003), and neuropeptides such as vasoactive intestinal polypeptide (VIP) (Petit et al, 1995;Kozicz et al, 1998) and cholecystokinin Seroogy and Fallon, 1989).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Anterograde tracing studies with Phaseolus vulgaris leucoagglutinin (PHA-L) or biotinylated dextran amine (BDA) have demonstrated that regions of the basal forebrain are heavily targeted by DRN projections (Vertes, 1991;Sim and Joseph, 1993;Morin and Meyer-Bernstein, 1999), and retrograde tracing has confirmed that this projection arises, in part, from nonserotonergic neurons (Descarries et al, 1986;Semba et al, 1988;Stratford and Wirtshafter, 1990;Li et al, 1990; Van Bockstaele et al, 1993;Petrov et al, 1994;Ford et al, 1995;Gasbarri et al, 1999; Hansue and Shammah-Lagnado, 2002;Halberstadt and Balaban, 2006a). A recent study combined BDA anterograde tracing with 5-HT-immunofluorescent staining to demonstrate that the vast majority of DRN fibers innervating the septum are nonserotonergic (Aznar et al, 2004).…”
Section: Nih Public Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…This cell group extends rostrocaudally for a little more than 0.5 mm, occupying the rostral third of this nucleus as defined by its content in 5HT neurons (Descarries et al, 1986). It begins rostral at the level of the oculomotor nucleus and reaches its greatest dimension at level A-770, and reduce abruptly at level A-470 (Steinbusch et al, 1980).…”
mentioning
confidence: 96%